Diametric calix[6]arene-based phosphine gold(I) cavitands - Giovanardi, Gabriele; Secchi, Andrea; Arduini, Arturo; Cera, Gianpiero (Beilstein Journal of Organic Chemistry, 2022)
We report the synthesis and characterization, in low polarity solvents, of a novel class of diametric phosphine gold(I) cavitands characterized by a 1,2,3-alternate geometry. Preliminary catalytic studies were performed on a model cycloisomerization of 1,6-enynes as a function of the relative orientation of the bonded gold(I) nuclei with respect to the macrocyclic cavity.
Keywords: 1,2,3-alternate conformation; calix[6]arenes; gold(I) catalysis; phosphines